Functional Metagenomics Characterization of an Anaerobic Saltwater Bioreactor. (2nd May 2019) - Derilus, D.; Forestil, A.; Fortuné, J.; Polyanska, O.; Louime, C.; Gervais, G.; Massey, S. E.
Abstract : Methanogens are restricted to a few genera of Archaea, however they have great importance in the carbon cycle, impacting climactic considerations, and also find a role in renewable energy in the form of biogas. Here, we examine the microbial contribution to the production of methane in a sargassum fed anaerobic saltwater bioreactor, which are poorly characterized compared to fresh water bioreactors, using a comprehensive functional metagenomics approach. Despite abundant production of methane, we detected a low proportion of Archaea in the system using 16S rRNA community profile analyses. We address the low representation using an additional 16S rRNA analysis of shotgun data and a consideration of CO2 :CH4 production. Using a novel network alignment and tree building approach, we measured similarity between the meta-metabolic capabilities of different anaerobic microbial communities. The saltwater bioreactor samples clustered together, validating the approach and providing a method of determining meta-metabolic similarity between microbial communities, with a range of potential applications. We also introduce a number of additional approaches for examining and interpreting meta-metabolic network topology. The low abundance of methanogens appears as a common property of such anaerobic systems and likely reflects the relatively poor energetics of methanogens, while examination of key enzymes confirms that hydrogen producing bacteria are the major fermentative guild. Our results indicate that the use of readily available seawater and marine macroalgae is a promising approach to the production of biogas as a source of renewable energy.